Asymmetric Aldol Reaction of Alkenyl Esters with α-Keto Esters Catalyzed by Chiral Tin Alkoxides - Yanagisawa, Akira; Uchiyama, Chika; Takagi, Kotaro (Synlett, 2021)
A catalytic enantioselective aldol reaction of alkenyl esters with α-keto esters was achieved by using an (R)-BINOL-derived chiral tin dibromide possessing 4-t-butylphenyl groups at the 3- and 3′-positions as a chiral precatalyst in the presence of sodium methoxide and methanol. Optically active aldol products possessing a chiral tertiary carbon were diastereoselectively obtained with up to 92% ee and moderate to high yields, not only from cyclic alkenyl esters, but also from acyclic ones under the influence of the chiral tin methoxide generated in situ.
Keywords: aldol reaction; alkenyl ester; asymmetric catalysis; α-keto esters; tin catalysis